Extracellular nucleic acids in monochloraminated drinking water distribution systems - Bairoliya, Sakcham (Nanyang Technological University, 2021)
The provision of safe drinking water is complicated by the presence of biofilms in the drinking water distribution pipeline. Presence of secondary disinfectant residuals such as monochloramine (MCA) could result in release of nucleic acids from these biofilms and the cells contained in the bulk water, which can persist as extracellular nucleic acids. Presence of significant amounts of extracellular nucleic acids in drinking water distribution systems could be a matter of both interest and concern. Removal of extracellular nucleic acids could make the monitoring of the DWDS microbiome more reliable, but at the same time, it might relay information that has previously not been considered. The objective of the study is to explore the occurrence, extraction, and quantification of extracellular nucleic acids in the DWDS. To test whether total DNA extracted from monochloraminated drinking water contains a substantial fraction of eDNA, drinking water samples were obtained from Locations 1 (~20-year-old pipeline) and 2 (~7-year-old pipeline). At Location 1, 85-386 ng of eDNA was found per litre of sampled water, which accounted for 52 ± 12 % of total DNA, while at Location 2, 33-58 ng of eDNA was found per litre of sampled water, accounting for 42 ± 8 % of the total DNA. Removal of eDNA reduced α-diversity, increased community evenness, and changed relative abundance of detected taxa. It was hypothesized that the interaction of MCA with pipe biofilms and bulk water cells resulted in the release of DNA in the DWDS. Testing the hypothesis required MCA preparation in the laboratory. The methods used for the synthesis of MCA at lab scale differ substantially in different studies and often lack a detailed protocol for MCA preparation. This makes it difficult to successfully replicate the preparation of MCA and compare results from studies using different protocols. Thus, four published protocols that are frequently used to prepare MCA in the environmental research community were compared. The results showed that the choice of protocol could result in substantial differences in decay kinetics and disinfection efficacy of the prepared MCA. Among the tested protocols, MCA prepared using liquid ammonia and bleach (Protocol 1 [P1]) showed minimal abiotic decay, good disinfection performance, and was a close representative of the MCA residue in an ideal DWDS. MCA prepared using P1 was used to investigate whether it can induce the release of nucleic acids from biofilms and planktonic cells. Using Pseudomonas aeruginosa as a model organism, it was observed that both DNA and RNA were released from the cells during MCA treatment. Surprisingly, the extracellular RNA (eRNA) was very stable and could persist for days. To further characterize the released nucleic acids, they were extracted and sequenced using next generation sequencing. Sequencing analysis revealed that eDNA could be used to assemble the whole genome of the model organisms, but some parts of the genome were more persistent than others. Analysis of eRNA revealed its potential as a signaling molecule in environmental systems and as a glimpse into the past metabolic state of the bacterial cells. To validate observations made in the lab-scale setup, the methods for eDNA and eRNA extraction from DWDS were optimized. Location 2 from the first study was used for sampling of drinking water, from which 56 ± 5 ng of eDNA and 143 ± 5 ng of eRNA per litre of water sampled was successfully extracted. The sequences of the extracellular nucleic acids (eNAC) from the DWDS were explored and the contribution of eNAC on the detected microbial community dynamics in DWDS was examined. Overall, this thesis work reports for the first time the persistence of a substantial amount of eNAC in DWDS and reveals the influence of eNAC on the sequencing-based profiling of DWDS microbiome. The presence of eNAC, in particular, the persistence of eRNA in DWDS, reported in this thesis work may lead to intriguing research questions regarding the fate and implication of eNAC in DWDS.